Evaluation of the iron-coating technology for direct-seeded rice in the Philippines - Cañete, Sandro D.; Collado, Wilfredo B.; Sashi, Kazumichi (2022)
Field and screenhouse experiments were conducted to evaluate the performance of iron-coated (Fe-coated) seeds in wet direct-seeded rice (DSR). Effects of iron-coating on seed germination and seedling establishment, yield performance, and the fate of added iron in rice and lowland soil were measured. The germination test disclosed that the mean maximum germination rates were almost similar between the coated and uncoated seeds across varieties, whereas the ironcoated seeds took a longer time to achieve the rates. Results confirmed that Fe-coated seeds produced more established seedlings at low seeding rates during the field experiment. Moreover, the effect of Fe-coating on yield was statistically similar to the transplanted rice and other wet direct seeding techniques, such as the use of dry and pre-germinated seeds regardless of the seeding rates and season. This implies that the seeding rate for wet DSR can be reduced using Fe-coated seeds without diminishing the yield. On the other hand, the screenhouse experiment disclosed a better seedling emergence response in the high flow rate with or without iron-coating.
Though yields were not influenced by the treatments, the Fe-coated seeds at a static flow rate achieved the highest yield among the treatments using the NSIC Rc222 variety. Furthermore, Fe-coating in rice seeds did not increase the level of Fe in the soil and in the aboveground plant biomass under wet direct seeding practice. Therefore, the use of Fe-coated seeds is highly regarded both in the wet direct seeding and water seeding practices to reduce the seeding rate while sustaining or improving the yields that are normally achieved under the conventional wet direct seeding practice in the country.
Keywords: Horticulture; Rice--Planting.